Manufacturing process of splashing color handicraft

In the color-splashing ceramic process, a process of spraying a single component paint with Tianna water to form a paint base, and then a mixed paint paste of copper, gold powder, silver powder and solvent to form a texture, and finally spraying film-forming substances such as PU bright oil. , solves the problem that the blank pigment is prone to cracking, deformation or glaze scar during high-temperature firing, improves the yield rate and imparts metallic luster and wear resistance to the coating.

CN119407928APending Publication Date: 2025-02-11QUANZHOU NANYANG ARTS & CRAFTS IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

During the production of underglaze color-splashed ceramics, the pigments on the blank are prone to cracking, deformation or glaze scars, which affect the yield rate.

Method used

Using a production process of color-splashing crafts, the paint base is formed by mixing single-component paint with Tianna water, spraying it into a paint base, and then spraying paint paste mixed with copper gold powder, silver powder and other paint powder with specific solvents to form paint points, and using natural droop The flow forms a golden and silver paste texture, and finally sprays film-forming substances such as PU bright oil to form a coating to avoid high temperature firing.

Benefits of technology

Through this process, problems such as cracking, deformation or glaze scars in the blank pigment during high-temperature firing are avoided, the yield of the handicraft is improved, and the coating is given metallic luster, hardness and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100899230000091
    Figure BDA0005100899230000091
Patent Text Reader

Abstract

The manufacturing process comprises the following steps: (1) mixing single-component paint and banana oil, and spraying the mixture on the surface of a green body to obtain a paint primer; (2) mixing bronze powder, banana oil, PU (Polyurethane) gloss oil, thinner and chemical bleaching water to obtain golden paint paste, dripping the golden paint paste on the paint base to form paint points, and enabling the paint points to naturally and vertically flow on the paint base to form golden paste textures; (3) mixing silver powder, banana oil, PU (polyurethane) gloss oil, ink thinner and chemical white water to obtain silver paint paste, dripping the silver paint paste on the golden paste texture to form paint points, and enabling the paint points to naturally and vertically flow on the golden paste texture to form silver paste texture; and (4) mixing PU gloss oil, banana oil, chemical white water and boiled water to form a mixed solution, and then spraying the mixed solution on the surface of the green body to obtain the splashing color handicraft. The splashing color handicraft obtained by the method is not subjected to high-temperature calcination, so that the problems of cracking, deformation or glaze scars and the like are avoided, and the yield of the handicraft is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of spraying technology, and in particular to a process for producing splash-color handicrafts. Background Art

[0002] Splash-color crafts are a type of artwork created by splashing paint and utilizing its natural flow and penetration properties, mainly in the two fields of underglaze splash-color ceramics and splash-color oil painting. Whether it is underglaze splash-color ceramics or splash-color oil painting, the splash-color process emphasizes the natural flow and penetration of colors, and utilizes the natural properties of colors after falling on paper or clay to create a unique artistic effect.

[0003] Among them, in the production process of underglaze splashed color ceramics, the usual steps include: first, adjust the pigment to the required hue and concentration and splash it on the ceramics, using its natural flow and penetration properties to form the general structure, and then use the shape and texture effects of color penetration to organize and supplement, and finally, outline and fill in colors after drying to complete the work.

[0004] In the production process of underglaze splash-color ceramics, during the high-temperature firing stage, the pigment on the body is prone to cracking, deformation, or glaze scarring, which in turn affects the yield rate. Summary of the invention

[0005] In order to improve the problem that the pigment on the blank is prone to cracking, deformation or glaze scarring, the present application provides a production process for splash-color handicrafts.

[0006] The present application provides a process for producing splash-color handicrafts, which adopts the following technical solution: A process for making a splash-color handicraft comprises the following steps: (1) uniformly mixing the single-component paint and thinner, spraying the mixture on the surface of the blank, and curing the mixture to obtain a paint primer; (2) mixing copper powder, thinner, PU varnish, oil-opening water and whitening water evenly to obtain a golden paint slurry, and dripping the golden paint slurry on the paint base formed in step (1) to form paint dots, with a distance of 3-3.5 mm between each paint dot and an amount of 0.5-0.7 g per paint dot. The paint dots naturally flow down on the paint base to form a golden slurry texture; (3) silver powder, thinner, PU bright oil, oil-opening water and whitening water are mixed evenly to obtain a silver paint slurry, and the silver paint slurry is sprinkled on the gold paste texture formed in step (2) to form paint dots, with a distance of 2-2.5 mm between each paint dot and an amount of 0.2-0.4 g for each paint dot. The paint dots naturally flow on the gold paste texture to form a silver paste texture; (4) PU bright oil, thinner, whitening water and oil-opening water are mixed evenly to form a mixed liquid, which is then sprayed on the surface of the blank and solidified to obtain a splash-color handicraft.

[0007] By adopting the above technical solution, the single-component paint and thinner are first mixed, the thinner dilutes the single-component paint, reduces the viscosity of the single-component paint, and makes the single-component paint easier to flow when sprayed. After curing, the thinner evaporates to form a uniform paint base.

[0008] Copper-gold powder, thinner, PU bright oil, oil-opening water and whitening water are mixed to obtain a golden paint slurry. The copper-gold powder gives the coating a metallic luster and color, providing a copper-gold metallic texture. The thinner, oil-opening water and whitening water are mixed to adjust the viscosity of the system so that the copper-gold powder and PU bright oil are evenly distributed in the system. The golden paint slurry subsequently forms a golden slurry texture. In addition, the PU bright oil increases the hardness, wear resistance and glossiness of the coating, protects the copper-gold powder, and extends the service life of the coating. By setting the amount and distance of the paint dots, the paint dots can influence each other during the vertical flow process, but they will not completely merge to form a texture.

[0009] Silver powder, thinner, PU bright oil, oil-opening water and whitening water are mixed to obtain a silver paint slurry. Silver powder gives the coating a metallic luster. Thinner, oil-opening water and whitening water are mixed as solvents to adjust the viscosity of the system so that the silver powder and PU bright oil are evenly distributed in the system. The obtained silver paint slurry subsequently forms a silver slurry texture. In addition, PU bright oil provides high gloss and good protective performance, protects the silver powder, and extends the service life of the coating. Further, by setting the amount and distance of paint dots, the paint dots can influence each other during the vertical flow process, but will not completely merge to form a texture.

[0010] Finally, PU bright oil, thinner, whitening water and oil-opening water are mixed evenly. PU bright oil is the main film-forming substance. After being mixed with thinner, whitening water and oil-opening water, a coating with high gloss and protection is formed. Thinner, whitening water and oil-opening water are used as solvents to reduce the viscosity of the system, making it easier to spray, ensuring the leveling and glossiness of the coating. The splash-color handicrafts obtained by the above method are not subjected to high-temperature calcination, so there will be no problems such as cracking, deformation or glaze scars, thereby improving the yield rate of handicrafts.

[0011] Preferably, in step (2), the golden paint slurry is dripped onto the surface of the paint base formed in step (1) at a distance of 5-5.5 mm from the blank.

[0012] By adopting the above technical solution, the distance between the golden paint slurry and the blank is further limited, so that the paint slurry is evenly distributed, dripping is reduced, and there is no splashing. Each paint point does not affect each other and will not affect the vertical flow effect of subsequent paint points.

[0013] Preferably, in step (3), the silver paint slurry is dripped onto the surface of the gold slurry texture formed in step (2) at a distance of 5-5.5 mm from the blank.

[0014] By adopting the above technical solution, the distance between the silver paint slurry and the blank is further limited, so that the paint slurry is evenly distributed, dripping is reduced, and there is no splashing. Each paint point does not affect each other and will not affect the vertical flow effect of subsequent paint points.

[0015] Preferably, the paint base thickness is 8-10 μm, the gold paste texture thickness is 5-7 μm, the silver paste texture thickness is 2-4 μm, and in step (4), the spraying thickness of the mixed solution is 1-3 μm.

[0016] By adopting the above technical solution, the paint base, gold paste texture, silver paste texture, and spraying thickness of the mixed liquid are further limited, and the splash color crafts obtained have better craftsmanship effects. The role of the paint base is to provide a uniform and smooth base to enhance the adhesion and overall effect of the subsequent coating. The gold paste and silver paste are used to create specific visual effects and textures to ensure the clarity of the texture and the stability of the coating. The spraying thickness of the mixed liquid ensures the protection and aesthetics of the coating.

[0017] Preferably, in step (1) and step (4), curing is performed at 35-38° C. for 2-3 hours.

[0018] By adopting the above technical solution, the solvent evaporates, leaving the solid components to form a continuous coating, further limiting the curing temperature and time, accelerating the curing efficiency, and improving the efficiency of handicraft preparation.

[0019] Preferably, in step (4), the raw material components of the mixed solution also include 0.2-0.4 parts of modified quartz powder.

[0020] By adopting the above technical solution, the addition of modified quartz powder can enhance the hardness, wear resistance, scratch resistance and chemical resistance of the solution system, while improving the adhesion of the coating, ensuring the stability and durability of the coating, and extending the service life of the crafts. The porous structure of the modified quartz powder makes the quartz powder have a good matting effect, which can improve the smoothness of the coating, reduce the glossiness, and meet specific visual effect requirements. In addition, the chemical properties of the modified quartz powder are stable and it is not easy to react with moisture, oxygen, etc. in the air. It can improve the chemical stability of the crafts and prevent color fading and material aging.

[0021] Preferably, the method for preparing the modified quartz powder comprises the following steps: (1) immersing the quartz powder in a hydrochloric acid solution with a mass concentration of 10-15% for 30-35 minutes, washing with water, and then calcining at a temperature of 600-650° C. for 1-1.5 hours, grinding, and sieving to obtain fine powder; (2) Dispersing the fine powder obtained in step (1) in deionized water, adding modified coconut shell fiber, sodium polycarboxylate, and cellulose acetate butyrate, stirring at a temperature of 80-85° C. for 1-2 h, filtering, and drying to obtain modified quartz powder.

[0022] By adopting the above technical solution, quartz powder is dispersed in a hydrochloric acid solution, and the hydrochloric acid reacts with metal impurities (such as iron, aluminum, etc.) in the quartz powder to dissolve them, thereby reducing the impurity content in the quartz powder and improving its purity. Then, calcination is performed at a temperature of 600-650°C to further remove impurities in the quartz powder, increase the specific surface area of ​​the quartz powder, and facilitate subsequent mixing with other components.

[0023] Modified coconut shell fiber has a high aspect ratio and good mechanical properties. It can be loaded on the surface of quartz powder and mixed with quartz powder to enhance the density of the structural system and improve the mechanical properties and wear resistance of quartz powder. The subsequently formed coating has good tensile strength, flexural strength and wear resistance, which improves its overall mechanical properties.

[0024] Sodium polycarboxylate is used as a dispersant to improve the fluidity and processing performance of the mixture, so that the quartz powder, modified coconut shell fiber and cellulose acetate butyrate are mixed evenly, and the density and strength of the mixture are improved. Cellulose acetate butyrate has a certain viscosity, which makes the modified coconut shell fiber adhere to the surface of the quartz powder, improves the stability of the mixture of modified coconut shell fiber and quartz powder, and makes the modified quartz powder have better mechanical properties. It is subsequently used in the coating to improve the viscosity, mechanical properties and wear resistance of the coating.

[0025] Preferably, the mass ratio of the quartz powder, modified coconut shell fiber and cellulose acetate butyrate is 1:0.5-0.7:0.1-0.2.

[0026] By adopting the above technical scheme, the mass ratio of quartz powder, modified coconut shell fiber and cellulose acetate butyrate is further limited within a certain range, and the mechanical properties and wear resistance of quartz powder are improved. The modified coconut shell fiber has a high aspect ratio and good mechanical properties, and can be loaded on the surface of quartz powder. Quartz powder has high hardness and chemical stability. The combination of the two improves the mechanical properties of quartz powder such as wear resistance, toughness, tensile strength and bending strength. Cellulose acetate butyrate provides good adhesion and processing properties, so that the modified coconut shell fiber adheres to the surface of quartz powder, and the modified quartz powder has good mechanical properties, which is subsequently applied to the coating to improve the viscosity, mechanical properties and wear resistance of the coating.

[0027] Preferably, the method for preparing the modified coconut shell fiber comprises the following steps: (1) soaking coconut shell fiber in sodium hydroxide solution, stirring for 20-30 minutes, then dispersing in deionized water, adding silane coupling agent, stirring at 60-65° C. for 1-2 hours, filtering, and drying to obtain pretreated coconut shell fiber; (2) immersing the nano-titanium dioxide in an ethanol solvent, stirring evenly, drying, and calcining at 300-350° C. for 1-2 hours to obtain pretreated nano-titanium dioxide; (3) Dispersing the coconut shell fiber pretreated in step (1) in deionized water, adding the nano-titanium dioxide and hydroxyethyl cellulose pretreated in step (2), stirring evenly, and drying to obtain modified coconut shell fiber.

[0028] By adopting the above technical scheme, sodium hydroxide treatment can effectively remove impurities such as wax and fatty acid residues on the surface of coconut shell fiber, improve the surface cleanliness and activity of the fiber, and thus improve the bonding between the fiber and other components. Silane coupling agent can form chemical bonds on the surface of coconut shell fiber and improve the surface activity of coconut shell fiber.

[0029] Nano-titanium dioxide is immersed in an ethanol solvent to improve the dispersibility of the nano-titanium dioxide and reduce particle agglomeration, and then calcined at 300-350° C. to improve the purity and activity of the nano-titanium dioxide, which is conducive to the subsequent compounding of the nano-titanium dioxide with other components.

[0030] The pretreated nano-titanium dioxide is loaded on the surface and pores of the pretreated coconut shell fiber to improve the mechanical properties of the coconut shell fiber. The hydroxyethyl cellulose has a certain viscosity, which makes the nano-titanium dioxide and the coconut shell fiber bond more closely, so that the nano-titanium dioxide is loaded on the surface of the coconut shell fiber to improve the mechanical properties of the coconut shell fiber. It is subsequently applied to quartz powder to improve the corresponding properties of the quartz powder, and subsequently improves the mechanical properties, photocatalytic activity, and UV protection of the coating.

[0031] Preferably, the mass ratio of the coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is 1:0.5-0.6:0.1-0.3.

[0032] By adopting the above technical scheme, the mass ratio of coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is further limited within a certain range, and the mechanical properties, wear resistance and UV protection ability of coconut shell fiber are improved. Coconut shell fiber has good mechanical properties, nano titanium dioxide has photocatalytic activity, UV protection ability and antibacterial properties, nano titanium dioxide is loaded on the surface and pores of coconut shell fiber, and the mechanical strength, toughness, wear resistance and weather resistance of coconut shell fiber are improved. Hydroxyethyl cellulose makes nano titanium dioxide and coconut shell fiber bond more tightly, improves the mechanical properties of coconut shell fiber, and subsequently improves the mechanical properties, photocatalytic activity and UV protection of the coating.

[0033] In summary, this application has the following beneficial effects: 1. In the present application, copper-gold powder, thinner, PU bright oil, oil-opening water and whitening water are mixed to obtain a golden paint slurry. The copper-gold powder gives the coating a metallic luster and color, and provides a copper-gold metallic texture. The thinner, oil-opening water and whitening water are mixed to adjust the viscosity of the system so that the copper-gold powder and PU bright oil are evenly distributed in the system. By setting the amount and distance of the paint dots, the paint dots can influence each other during the vertical flow process, but will not completely merge to form a texture.

[0034] 2. In the present application, silver powder, thinner, PU varnish, oil-opening water and whitening water are mixed to obtain a silver paint slurry. The silver powder gives the coating a metallic luster. The thinner, oil-opening water and whitening water are mixed as a solvent to adjust the viscosity of the system so that the silver powder and PU varnish are evenly distributed in the system. Further, by setting the amount and distance of the paint dots, the paint dots can influence each other during the vertical flow process, but will not completely merge to form a texture.

[0035] 3. In the present application, PU bright oil, thinner, whitening water and oil-opening water are mixed evenly. PU bright oil, as the main film-forming substance, forms a coating with high gloss and protection after being mixed with thinner, whitening water and oil-opening water. The splash-color handicrafts obtained by the above method are not subjected to high-temperature calcination, so there will be no problems such as cracking, deformation or glaze scars, thereby improving the yield of handicrafts. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0038] Preparation example of modified quartz powder Preparation Example 1-1 The preparation method of modified quartz powder comprises the following steps: (1) 1.1 kg of quartz powder was soaked in 2 L of 13% hydrochloric acid solution for 33 min, washed with water, and then calcined at 640° C. for 1.5 h, ground, and passed through a 30-mesh sieve to obtain fine powder; (2) The fine powder obtained in step (1) was dispersed in 2.1 L of deionized water, and modified coconut shell fiber, 0.2 kg of sodium polycarboxylate, and cellulose acetate butyrate were added. The mixture was stirred at 85° C. for 1.5 h, filtered, and dried to obtain modified quartz powder.

[0039] The mass ratio of quartz powder, modified coconut shell fiber and cellulose acetate butyrate is 1:0.7:0.2.

[0040] The preparation method of modified coconut shell fiber comprises the following steps: (1) 1.0 kg of coconut shell fiber was soaked in 2 L of 10% sodium hydroxide solution, stirred for 25 min, then dispersed in 2 L of deionized water, 0.2 kg of silane coupling agent KH560 was added, stirred at 65 ° C for 1.5 h, filtered, and dried to obtain pretreated coconut shell fiber; (2) immersing the nano-titanium dioxide in 1.5 L of ethanol solvent, stirring evenly, drying, and calcining at 320° C. for 1.5 h to obtain pretreated nano-titanium dioxide; (3) Dispersing the coconut shell fiber pretreated in step (1) in 3 L of deionized water, adding the nano-titanium dioxide and hydroxyethyl cellulose pretreated in step (2), stirring evenly, and drying to obtain modified coconut shell fiber.

[0041] The mass ratio of coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is 1:0.6:0.3.

[0042] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified coconut shell fiber is added.

[0043] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), cellulose acetate butyrate is not added.

[0044] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of quartz powder, modified coconut shell fiber and cellulose acetate butyrate is 1:0.5:0.1.

[0045] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of quartz powder, modified coconut shell fiber and cellulose acetate butyrate is 1:0.1:0.4.

[0046] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of the modified coconut shell fiber, no nano titanium dioxide is added.

[0047] Preparation Example 1-7 The difference from Preparation Example 1-1 is that hydroxyethyl cellulose is not added in the preparation method of the modified coconut shell fiber.

[0048] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is 1:0.5:0.1.

[0049] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is 1:0.1:0.5. Example

[0050] Example 1 A process for making a splash-color handicraft comprises the following steps: (1) Mix 1 g of a one-component paint and 0.7 g of thinner evenly, spray the mixture on the surface of the body, and solidify the mixture to obtain a paint primer; (2) 1 g of 1000 mesh copper powder, 0.6 g of thinner, 0.4 g of PU varnish, 0.2 g of oil-opening water and 0.1 g of whitening water were mixed evenly to obtain a golden paint slurry, and the golden paint slurry was sprinkled on the paint base formed in step (1) to form 5 paint dots, with a distance of 3 mm between each paint dot and a dosage of 0.5 g for each paint dot. The paint dots naturally flowed on the paint base to form a golden slurry texture; (3) 1 g of 1000 mesh silver powder, 0.7 g of thinner, 0.3 g of PU varnish, 0.1 g of oil-opening water and 0.1 g of whitening water were mixed evenly to obtain a silver paint slurry, and the silver paint slurry was sprinkled on the gold paste texture formed in step (2) to form paint dots, with a distance of 2 mm between each paint dot and a dosage of 0.4 g for each paint dot. The paint dots naturally flowed on the gold paste texture to form a silver paste texture; (4) 1 g of PU bright oil, 0.3 g of thinner, 0.3 g of whitening water and 0.05 g of oil-opening water are mixed evenly to form a mixed liquid, which is then sprayed on the surface of the blank and solidified to obtain a splash-color handicraft.

[0051] In step (2), the golden paint slurry is put into an extruded plastic bottle, the bottle mouth is cut at an angle of 15° with a utility knife, and the golden paint slurry is dripped through the bottle mouth at a distance of 5 mm from the blank onto the surface of the paint base formed in step (1).

[0052] In step (3), the silver paint slurry is put into an extruded plastic bottle, the bottle mouth is cut at an angle of 15° with a utility knife, and the silver paint slurry is dripped through the bottle mouth at a distance of 5 mm from the blank onto the surface of the gold paint texture formed in step (2).

[0053] The thickness of the paint base is 8 μm, the thickness of the gold paste texture is 5 μm, and the thickness of the silver paste texture is 4 μm. In step (4), the spraying thickness of the mixed liquid is 1 μm.

[0054] In step (1) and step (4), curing is carried out at 35° C. for 2 h.

[0055] Example 2 A process for making a splash-color handicraft comprises the following steps: (1) 1.2 g of one-component paint and 0.9 g of thinner were mixed evenly, sprayed on the surface of the blank, and cured to obtain a paint primer; (2) 1.3 g of 1000 mesh copper powder, 0.7 g of thinner, 0.5 g of PU varnish, 0.3 g of oil-opening water and 0.2 g of whitening water were mixed evenly to obtain a golden paint slurry, and the golden paint slurry was sprinkled on the paint base formed in step (1) to form 5 paint dots, with a distance of 3.5 mm between each paint dot and a dosage of 0.7 g for each paint dot. The paint dots naturally flowed on the paint base to form a golden slurry texture; (3) 1.1 g of 1000 mesh silver powder, 0.7 g of thinner, 0.3 g of PU varnish, 0.2 g of oil-opening water and 0.3 g of whitening water were mixed evenly to obtain a silver paint slurry, and the silver paint slurry was dripped on the gold paste texture formed in step (2) to form paint dots, with a distance of 2.5 mm between each paint dot and a dosage of 0.2 g for each paint dot. The paint dots naturally flowed on the gold paste texture to form a silver paste texture; (4) 1 g of PU bright oil, 0.4 g of thinner, 0.4 g of whitening water and 0.08 g of oil-opening water are mixed evenly to form a mixed liquid, which is then sprayed on the surface of the blank and solidified to obtain a splash-color handicraft.

[0056] In step (2), the golden paint slurry is put into an extruded plastic bottle, the bottle mouth is cut at an angle of 15° with a utility knife, and the golden paint slurry is dripped through the bottle mouth at a distance of 5.5 mm from the blank onto the surface of the paint base formed in step (1).

[0057] In step (3), the silver paint slurry is put into an extruded plastic bottle, the bottle mouth is cut at an angle of 15° with a utility knife, and the silver paint slurry is dripped through the bottle mouth at a distance of 5.5 mm from the blank onto the surface of the gold paint texture formed in step (2).

[0058] The thickness of the paint base is 10 μm, the thickness of the gold paste texture is 7 μm, and the thickness of the silver paste texture is 2 μm. In step (4), the spraying thickness of the mixed liquid is 3 μm.

[0059] In step (1) and step (4), curing is carried out at 38°C for 3 hours.

[0060] Example 3 A process for making splash-color handicrafts, which differs from Example 1 in that, in step (4), the raw material components of the mixed solution also include 0.2-0.4 parts of modified quartz powder, and the modified quartz powder is prepared using Preparation Example 1-1.

[0061] Example 4 A process for making splash-color handicrafts, which differs from Example 3 in that, in step (4), the raw material components of the mixed solution also include 0.2-0.4 parts of modified quartz powder.

[0062] Example 5 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Example 1-2.

[0063] Example 6 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-3.

[0064] Example 7 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-4.

[0065] Example 8 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-5.

[0066] Example 9 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-6.

[0067] Example 10 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-7.

[0068] Embodiment 11 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-8.

[0069] Example 12 A process for making splash-color handicrafts, which differs from Example 3 in that the modified quartz powder is prepared using Preparation Examples 1-9.

[0070] Comparative Example Comparative Example 1 A process for making splash-color handicrafts, which differs from Example 1 in that in step (4), thinner is not added.

[0071] Comparative Example 2 A process for making splash-color handicrafts, which differs from Example 1 in that, in step (4), no whitening water is added.

[0072] Comparative Example 3 A process for making splash-color handicrafts, which differs from Example 1 in that, in step (4), no boiling oil water is added.

[0073] Performance testing The splash-color crafts prepared in Examples 1-12 and Comparative Examples 1-3 were subjected to performance tests. Mechanical properties test: After the sample is conditioned in a constant temperature and humidity chamber at 25°C and 40% relative humidity for 24 hours, the tensile strength is tested according to ISO527-2012, the tear strength is tested according to ISO 6383-1:1983, and the impact strength is tested according to ISO179-1-2010.

[0074] Adhesion test: According to the GB1720-2020 method, the coating integrity within the range of the circular roller line scratch is rated.

[0075] Abrasion test: The coating abrasion resistance test was carried out in accordance with GB / T1768-2006. The test results are shown in Table 1.

[0076] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the splash-color crafts prepared in Examples 1-2 of the present application have good glossiness, and the coating formed by spraying the mixed liquid on the surface of the blank has good mechanical properties, wear resistance and mechanical strength. Among them, the tensile strength of Example 1 is 1.8MPa, the tear strength is 1.5MPa, and the impact strength is 1.2KJ / m 2 The adhesion is level 2, and the wear resistance is 0.034g, which means that the use of white water, whitening water and oil-opening water as solvents reduces the viscosity of the system, making it easier to spray and ensuring the leveling and glossiness of the coating. The splash-color handicrafts obtained by the above method are not subjected to high-temperature calcination, so there will be no problems such as cracking, deformation or glaze scars, thereby improving the yield of handicrafts.

[0077] The raw material components of the mixed solution in Example 3-4 also include modified quartz powder. It can be seen from Table 1 that compared with Example 1, the tensile strength of Example 3 is 5.2MPa, the tear strength is 4.9MPa, and the impact strength is 4.7KJ / m 2 , adhesion is level 1, and wear resistance is 0.012g, which means that the addition of modified quartz powder can enhance the hardness, wear resistance, scratch resistance and chemical resistance of the solution system, while improving the adhesion of the coating and extending the service life of the handicraft. Moreover, the porous structure of the modified quartz powder can improve the smoothness of the coating, reduce the gloss, and is not easy to react with moisture and oxygen in the air. It can improve the chemical stability of the handicraft and prevent color fading and material aging.

[0078] In the preparation method of modified quartz powder in Example 5, modified coconut shell fiber is not added. As can be seen from Table 1, compared with Example 1, the tensile strength is 3.1 MPa, the tear strength is 2.8 MPa, and the impact strength is 2.5 KJ / m 2, the adhesion is level 1, and the wear resistance is 0.025g, which shows that the modified coconut shell fiber has a high aspect ratio and good mechanical properties. It can be loaded on the surface of quartz powder and mixed with quartz powder to enhance the density of the structural system and improve the mechanical properties and wear resistance of quartz powder. The coating formed subsequently has good tensile strength, flexural strength, and wear resistance, which improves its overall mechanical properties.

[0079] In the preparation method of modified quartz powder in Example 6, cellulose acetate butyrate is not added. As can be seen from Table 1, compared with Example 1, the tensile strength is 3.8 MPa, the tear strength is 3.6 MPa, and the impact strength is 3.3 KJ / m 2 , adhesion is level 1, and wear resistance is 0.020g, indicating that cellulose acetate butyrate has a certain viscosity, which makes the modified coconut shell fiber adhere to the surface of quartz powder, improves the stability of the mixture of modified coconut shell fiber and quartz powder, and makes the modified quartz powder have better mechanical properties, which can be subsequently used in coatings to improve the viscosity, mechanical properties and wear resistance of the coatings.

[0080] Examples 7-8 change the mass ratio of quartz powder, modified coconut shell fiber, and cellulose acetate butyrate. It can be seen from Table 1 that compared with Example 3, the tensile strength, tear strength, impact strength and wear resistance of Example 8 are better than those of Examples 5-6, but worse than those of Example 3 and Example 7, indicating that cellulose acetate butyrate provides good adhesion and processing properties, so that the modified coconut shell fiber adheres to the surface of the quartz powder, and the modified quartz powder has better mechanical properties, which is subsequently applied to the coating to improve the viscosity, mechanical properties and wear resistance of the coating.

[0081] In the preparation method of Example 9 modified coconut shell fiber, nano titanium dioxide is not added. As can be seen from Table 1, compared with Example 3, the tensile strength is 3.3 MPa, the tear strength is 3.1 MPa, and the impact strength is 2.8 KJ / m 2 , adhesion is level 1, and wear resistance is 0.020 g, indicating that nano-titanium dioxide has strength, photocatalytic activity, UV protection and antibacterial properties. Nano-titanium dioxide is loaded on the surface and pores of coconut shell fiber, thereby improving the mechanical properties of modified coconut shell fiber and thus improving the comprehensive performance of the coating.

[0082] In the preparation method of modified coconut shell fiber in Example 10, hydroxyethyl cellulose is not added. As can be seen from Table 1, compared with Example 3, the tensile strength is 3.7 MPa, the tear strength is 3.5 MPa, and the impact strength is 3.2 KJ / m 2The adhesion is level 1 and the wear resistance is 0.021g, which shows that hydroxyethyl cellulose has a certain viscosity, which makes the nano-titanium dioxide and coconut shell fiber bond more closely, so that the nano-titanium dioxide is loaded on the surface of the coconut shell fiber, improving the mechanical properties of the coconut shell fiber, and then applied to quartz powder to improve the corresponding properties of the quartz powder, and then improve the mechanical properties, photocatalytic activity and UV protection of the coating.

[0083] Examples 11-12 change the mass ratio of coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose. It can be seen from Table 1 that compared with Example 3, the tensile strength, tear strength, impact strength and wear resistance of Example 12 are better than those of Examples 9-10, but worse than those of Examples 3 and 10, indicating that nano titanium dioxide is loaded on the surface and pores of coconut shell fiber, thereby improving the mechanical strength, toughness, wear resistance and weather resistance of coconut shell fiber, and hydroxyethyl cellulose makes nano titanium dioxide and coconut shell fiber bond more closely, thereby improving the mechanical properties of coconut shell fiber, and subsequently improving the mechanical properties, photocatalytic activity and ultraviolet protection of the coating.

[0084] In step (4) of Comparative Examples 1-3, thinner, whitening water, and oil-opening water are not added. As can be seen from Table 1, compared with Example 1, the tensile strength, tear strength, impact strength, and abrasion resistance are all worse than those of Example 1-2, indicating that the PU bright oil, thinner, whitening water, and oil-opening water are mixed evenly. The PU bright oil, as the main film-forming substance, forms a coating with high gloss and protective properties after being mixed with thinner, whitening water, and oil-opening water. The thinner, whitening water, and oil-opening water are used as solvents to reduce the viscosity of the system, making it easier to spray, and ensuring the leveling and glossiness of the coating. Thinner is used to increase the viscosity of the solution, making it easier to apply, whitening water is used to prevent the solution from turning white in a humid environment, and oil-opening water is used to extend the open time of the solution, allowing it to have more time to flow and solidify.

[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for making splash-color handicrafts, characterized in that: The steps include: (1) Mix the single-component paint and thinner evenly, spray them on the surface of the blank, and solidify them to obtain a paint primer; (2) Mix the copper powder, thinner, PU bright oil, oil-opening water and whitening water evenly to obtain a golden paint slurry, and sprinkle the golden paint slurry on the paint base formed in step (1) to form paint dots, with a distance of 3-3.5 mm between each paint dot and an amount of 0.5-0.7 g for each paint dot. The paint dots naturally flow down on the paint base to form a golden slurry texture; (3) Silver powder, thinner, PU bright oil, oil-opening water and whitening water are mixed evenly to obtain a silver paint slurry, and the silver paint slurry is sprinkled on the gold paste texture formed in step (2) to form paint dots, with a distance of 2-2.5 mm between each paint dot and a paint dosage of 0.2-0.4 g for each paint dot. The paint dots naturally flow on the gold paste texture to form a silver paste texture; (4) Mix PU bright oil, thinner, whitening water and oil-opening water evenly to form a mixed liquid, and then spray it on the surface of the blank and solidify it to obtain a splash-color handicraft.

2. The process for making a splash-color handicraft according to claim 1, characterized in that: In step (2), the golden paint slurry is dripped onto the surface of the paint base formed in step (1) at a distance of 5-5.5 mm from the blank.

3. The process for making a splash-color handicraft according to claim 1, characterized in that: In step (3), the silver paint slurry is dripped onto the surface of the gold slurry texture formed in step (2) at a distance of 5-5.5 mm from the blank.

4. The process for making a splash-color handicraft according to claim 1, characterized in that: The thickness of the paint base is 8-10 μm, the texture thickness of the gold paste is 5-7 μm, the texture thickness of the silver paste is 2-4 μm, and in step (4), the spraying thickness of the mixed solution is 1-3 μm.

5. The process for making a splash-color handicraft according to claim 1, characterized in that: In step (1) and step (4), curing is carried out at 35-38°C for 2-3 hours.

6. The process for making a splash-color handicraft according to claim 1, characterized in that: In step (4), the raw material components of the mixed solution also include 0.2-0.4 parts of modified quartz powder.

7. The process for making a splash-color handicraft according to claim 6, characterized in that: The preparation method of the modified quartz powder comprises the following steps: (1) Soak the quartz powder in a hydrochloric acid solution with a mass concentration of 10-15% for 30-35 minutes, wash with water, and then calcine at a temperature of 600-650°C for 1-1.5 hours, grind, and sieve to obtain fine powder; (2) Dispersing the fine powder obtained in step (1) in deionized water, adding modified coconut shell fiber, sodium polycarboxylate and cellulose acetate butyrate, stirring at a temperature of 80-85° C. for 1-2 h, filtering and drying to obtain modified quartz powder.

8. The process for making a splash-color handicraft according to claim 7, characterized in that: The mass ratio of the quartz powder, the modified coconut shell fiber and the cellulose acetate butyrate is 1:0.5-0.7:0.1-0.

2.

9. The process for making a splash-color handicraft according to claim 7, characterized in that: The preparation method of the modified coconut shell fiber comprises the following steps: (1) Soaking coconut shell fiber in sodium hydroxide solution, stirring for 20-30 minutes, then dispersing in deionized water, adding silane coupling agent, stirring at 60-65° C. for 1-2 hours, filtering, and drying to obtain pretreated coconut shell fiber; (2) immersing the nano-titanium dioxide in an ethanol solvent, stirring evenly, drying, and calcining at 300-350° C. for 1-2 hours to obtain pretreated nano-titanium dioxide; (3) Dispersing the coconut shell fiber pretreated in step (1) in deionized water, adding the nano-titanium dioxide and hydroxyethyl cellulose pretreated in step (2), stirring evenly, and drying to obtain modified coconut shell fiber.

10. The process for making a splash-color handicraft according to claim 9, characterized in that: The mass ratio of the coconut shell fiber, nano titanium dioxide and hydroxyethyl cellulose is 1:0.5-0.6:0.1-0.3.